Correction: Recombinant Yellow Fever Viruses Elicit CD8+ T Cell Responses and Protective Immunity against Trypanosoma cruzi. - Raquel Tayar Nogueira; Alanderson Rocha Nogueira; Mirian Claudia Souza Pereira; Maurício Martins Rodrigues; Patrícia Cristina da Costa Neves; Ricardo Galler; Myrna Cristina Bonaldo (PLoS ONE, 2013)
[This corrects the article DOI: 10.1371/journal.pone.0059347.].